Application of Single Program Ko - Factor for Instrumental Neutron Activation Analysis (INAA) - Mohammad, Kareem K; Hashem, Dunia A; Al-Jaaf, Jassim M (Al-Nahrain Journal of Science, 2018)
In this present work a computer program has been design to calculate the concentrations of elements by instrumental neutron activation analysis (INAA) using a single comparator method ( K_° -factor). A neutron source of 14 MeV was used as an irradiation source. irradiated samples were measured by a multi- channel system connected to high-purity germanium (HPGe) detector of high efficiency and an energy resolution of 1.9 KeV for Co-60 isotopes (1332KeV). Aluminum foils (AL-27) have been irradiation to calculate the neutron flux. Other samples were also in vales to gaiters like Au,Zr foil and used for neutron flux monitoring procedures. Result of concentrations were in agreement with theoretical predications and experimental measurements of previous studies and an accurate with 10%.